Reliability and concurrent validity between two-dimensional and three-dimensional evaluations of knee valgus during drop jumps - Ortiz, A.; Rosario-Canales, M.; Rodriguez, A.; Seda, A.; Figueroa, C.; Venegas-Rios, H. L. (Open Access Journal of Sports Medicine, 2016)
The aim of this study was to establish the concurrent validity and reliability of four different two-dimensional (2D) video-based techniques for quantifying frontal plane knee kinematics during a 40 cm double-legged drop jump. Participants and methods: A convenience sample of 16 healthy participants (nine males and seven females; age: [mean ± standard deviation] 25.5±2 years; body mass index: 24.33±2.98 kg/m2) participated in this investigation. A total of five trials during a 40 cm drop jump maneuver with a countermovement jump were used as the functional task. Four knee valgus measures, such as two different frontal plane projection angle measures, knee-to-ankle separation ratio (KASR), and knee separation distance (KSD), were measured using 2D and three-dimensional (3D) systems. To generalize to the greater population of possible evaluators, the testers performing the biomechanical analyses were three novice physical therapists. Intra- and intertester intraclass correlation coefficients (ICCs) were estimated for 2D analysis variables. ICCs were estimated for all measures between systems to determine concurrent validity of the 2D system. Results: All four 2D measures showed good to excellent reliability (ICC: 0.89-0.99). KASR and KSD showed excellent correlation (ICC: 0.96; 95% CI: 0.82-0.98 and ICC: 0.94; 95% CI: 0.90-0.96, respectively) with the 3D system, while both methods of frontal plane projection angle showed poor to moderate correlation (ICC: 0-0.57) with the 3D system. Conclusion: 2D KASR and KSD measures are cost effective, reliable, and highly correlated with the same measures using 3D techniques for the evaluation of knee valgus.